Biological Invasions in South Africa 2020
DOI: 10.1007/978-3-030-32394-3_11
|View full text |Cite
|
Sign up to set email alerts
|

Biological Invasions in South Africa’s Urban Ecosystems: Patterns, Processes, Impacts, and Management

Abstract: As in other parts of the world, urban ecosystems in South Africa have large numbers of alien species, many of which are invasive. Whereas invasions in South Africa's natural systems are strongly structured by biotic and abiotic features of the region's biomes, the imprint of these features is much less marked in urban ecosystems that exist as islands of human-dominated and highly modified habitat. Surprisingly little work has been done to document how invasive species spread in South African urban ecosystems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 131 publications
2
28
0
Order By: Relevance
“…Ogden et al 2019). The remaining chapters focus on specific areas that are invaded-freshwater ecosystems (Weyl et al 2020), coastal marine ecosystems (Robinson et al 2020), offshore sub-Antarctic islands (Greve et al 2020), and urban settings (Potgieter et al 2020). Most invasive alien species in South Africa are plants (Table 1.1), and these are consequently best understood.…”
Section: Scope and Arrangement Of This Bookmentioning
confidence: 99%
“…Ogden et al 2019). The remaining chapters focus on specific areas that are invaded-freshwater ecosystems (Weyl et al 2020), coastal marine ecosystems (Robinson et al 2020), offshore sub-Antarctic islands (Greve et al 2020), and urban settings (Potgieter et al 2020). Most invasive alien species in South Africa are plants (Table 1.1), and these are consequently best understood.…”
Section: Scope and Arrangement Of This Bookmentioning
confidence: 99%
“…11). Sus scrofa damages some critically endangered plants in the Western Cape, affecting succession and facilitating alien plant spread (Picker and Griffiths 2011). Capra hircus grazing has reduced the cover and density of endemic geophytes and succulents shrubs in thicket vegetation, and conservation of this endemic-rich flora is seriously threatened (Moolman and Cowling 1994).…”
Section: Mammalsmentioning
confidence: 99%
“…A co-ordinated strategy to deal with PSHB in South Africa will require a revision of legislation and the creation of policies pertaining to biological invasions. Currently, there is no co-ordinated management of invaders in urban ecosystems (Potgieter et al 2020), a critical oversight as shown in this study. The governance of IAS in general, and PSHB in particular, would require re-alignment of priorities between various spheres of government and enhanced involvement of private actors.…”
Section: Discussionmentioning
confidence: 90%
“…Given that the invasion in South Africa is at an early stage, very little is known about both its current and possible unmitigated spread and impact. As has been the case in other parts of the world (Gaertner et al 2017), little attention has been paid to assessing the impacts of biological invasions in urban ecosystems of South Africa (Potgieter et al 2020). One source estimates that if all of Johannesburg's 10 million urban trees are affected, it may have an impact of over R50bn if these trees need to be removed, chopped, chipped and replanted with more resistant species (DAFF 2020a).…”
Section: Introductionmentioning
confidence: 99%